FOREWORD - (Chief-in-Editor), Masduki (Journal of Research and Advances in Mathematics Education, 2016)
Welcome to volume 1 issue 1 of Journal of Research and Advances in Mathematics Education (JRAMathEdu). JRAMathEdu is  open-access and peer-reviewed scholarly journal managed by Department of Mathematics Education, Universitas Muhammadiyah Surakarta and published by Muhammadiyah University Press (MUP). The journal is designed and devoted to publish  high scientific value research papers of lecturers, researchers, university students (graduate or undergraduate), and teachers in mathematics education area. The journal publishes research papers in the fields of  learning mathematics,  instructional method in mathematics, innovations in teaching mathematics, evaluation and assesment in mathematics learning, developing technology  in mathematics education, developing and evaluation of mathematics curriculum, mathematics and culture, psychology in mathematics education, and other issues in mathematics education area that have a global perspective than local interest. The articles should be original, unpublished, and not in consideration for publication elsewhere at the time of submission to the JRAMathEdu. The journal is published twice a year in January and July.